O exame da constitucionalidade da utilização dos paraísos fiscais como instrumento de planejamento tributário - Farias, Rui Barros Leal (2007)
The current study proposes to examine a subject until this moment poorly focused by the Tax Law studies in Brazil. The aim is to examine the constitutionality of the use of tax heavens as a tax planning form. At the first moment, is discussed the practice of tax planning in face of the Federal Constitution of 1.988. In the second moment, it seeks the identification of all elements that characterize the tax heavens, in the Brazilian legal regime as well as in other legal regimes, exposing that the criteria used is not uniform. In regards to the national Law, all of the legal prevision regulating the subject in this matter are commented, explaining that since there are no legal or constitutional obstacles, the tax payer has the right to use the tax heavens, respecting the limitations imposed by the Brazilian legal system. At last, the jurisdictions reported as tax heavens are examined, exposing the particularities that make them to be considered as such.